Auxiliary elements of mammalian pre-mRNAs polyadenylation signals - Zarudnaya, M.I.; Potyahaylo, A.L.; Kolomiets, I.M.; Hovorun, D.M. (Біополімери і клітина, 2002)
Polyadenylation is one of the levels at which eukaryotic gene expression is regulated. The auxiliary elements of mammalian polyadenylation (poly(A)) signals are known to influence positively or negatively the efficiency of 3'-end processing. In this paper, we surveyed the literature on auxiliary elements of mammalian poly(A) signals. We also compiled the database of human poly(A) signals and searched it for auxiliary elements. This database contains 244 pre-mRNA sequences covering the cleavage region. Literature data and our database screen demonstrated that auxiliary elements, particularly, sequences binding Ul snRNP-specific UJ A protein, are widely presented in cellular pre-mRNAs. Besides, we analyzed our database for the availability of the polynucleotide sequences with a potential to form G-quadruplexes or i-motifs which we consider as possible auxiliary elements. Based on published experimental findings on formation of quadruplexes, the schematic structures of possible quadruplexes are proposed for several human pre-mRNAs. The structures of putative quadruplexes are oho represented for G-rich auxiliary downstream element of SV40 L poly(A) signal Поліаденілування – один з клітинних процесів, на рівні яких відбувається регуляція експресії генів. Допоміжні елементи полі(А)-сигналів про-мРНК ссавців стимулюють або пригнічують реакцію поліаденілування, що спрямовується кор-елементами сигналів. У цій роботі ми обговорюємо структуpy і функції відомих в літературі допоміжних елементів та проводимо їхній пошук у створеній нами базі даних полі(А)-сигналів про-мРНК людини, яка містить 244 послідовності про-мРНК в області місця розщеплення. Аналіз літератури і створеної бази даних свідчить про широку поширеність у клітинних про-мРНК допоміжних елементів, зокрема послідовностей, що зв'язують VI мяРНП-специфічний VIA білок. Окрім того, в створеній базі даних здійснено пошук послідовностей про-мРНК, які можуть утворювати чотирьохланцюгові структури (G-квадруплекси або і-мотиви). Ми припустили, що такі структури здатні виконувати деякі функції допоміжних елементів. У роботі наведено моделі квадруплексів для фрагментів деяких про-мРНК людини, які грунтуються на аналізі літератури, присвяченій чотирьохспіральним структурам, а також моделі G-квадруплексів для допоміжного G-багатого елемента полі(А)-сигналу про-мРНК SV40 L. Полиаденилирование – один из клеточных процессов, на уровне которых происходит регулирование экспрессии генов. Дополнительные элементы поли(А)-сигналов про-мРНК млекопитающих стимулируют или ингибируют реакцию полиаденилирования, направляемую кор-элементами. В этой работе мы обсуждаем структуру и функции известных в литературе дополнительных элементов и проводим их поиск в созданной нами базе данных поли(А)-сигналов про-мРНК человека, содержащей 244 последовательности про-мРНК в области места расщепления. Анализ литературы и созданной базы данных указывает на широкое распространение в клеточных про-мРНК дополнительных элементов, в частности последовательностей, связывающих VI мяРНП-специфичный VIA белок. Кроме того, в созданной базе данных проведен поиск последовательностей про-мРНК, способных образовывать четырехцепочечные структуры (G-квадруплексы или i-мотивы). Мы предположили, что такие структуры могут выполнять некоторые функции дополнительных элементов. В работе приведены модели квадруплексов для фрагментов некоторых про-мРНК человека, основанные на анализе литературы, посвященной четырехспиральным структурам, а также модели G-квадруплексов для дополнительного G-богатого элемента поли(А)-сигнала промРНК SV40 L.